Emissions Of Greenhouse Gases From Diesel Consumption In Agricultural Production Of Turkey - ADAY, Beran; ERTEKIN, Can; EVRENDILEK, Fatih (European Journal of Sustainable Development, 2016)
Agricultural sector is both energy consumer in the form of human labor, fossil fuels, electricity, seeds, fertilizer, and pesticides and energy producer in the form of food, feed, and biofuels. High agricultural use of energy inputs results in adverse environmental issues such as global climate change, pollution of water, soil and air, and unsustainable agricultural production. In this study, 35 agricultural crops such as cereals, fruits, and vegetables were evaluated in terms of consumption of diesel fuel during their production process including soil preparation, fertilization, sowing, spraying, harvesting and transportation, based on minimum and maximum values reported in related literature. Greenhouse gas (GHG) emissions from diesel consumption can be expressed as total carbon dioxide equivalent (CO2eq) emissions (2.76 kg per liter). a map showing total CO2eq emissions from diesel consumption for agricultural production. Our estimates showed that minimum and maximum GHG emissions varied between 0.48 and 3.75 Tg CO2eq for wheat, 17.15 and 65.45 Gg CO2eq for chickpea, and 0.088 and 0.153 Tg CO2eq for tomatoes, respectively. In order to reduce diesel-related GHG emissions, there is an urgent need for innovative agricultural practices and technologies to be put into place.